On the Economic Origins of Restrictions on Women's Sexuality - Anke Becker (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper studies the origins and function of customs aimed at restricting women's sexuality, such as a particularly invasive form of female genital cutting, restrictions on women's freedom of mobility, and norms about their sexual behavior. The analysis tests the anthropological theory that a particular form of pre-industrial subsistence – pastoralism – favored the adoption of such customs. Pastoralism was characterized by heightened paternity uncertainty due to frequent and often extended periods of male absence from the settlement, implying larger payoffs to imposing restrictions on women's sexuality. Using within-country variation across 500,000 women in 34 countries, the paper shows that women from historically more pastoral societies (i) are significantly more likely to have undergone infibulation, the most invasive form of female genital cutting; (ii) adhere to more restrictive norms about women's promiscuity; (iii) are more restricted in their freedom of mobility. Instrumental variable estimations that make use of the ecological determinants of pastoralism support a causal interpretation of the results. The paper further shows that the mechanism behind these patterns is indeed male absence, rather than male dominance, per se, or historical economic development.
Keywords: I15; N30; Z13; 330; infibulation; female sexuality; paternity uncertainty; concern about women's chastity